Effect of Giving Turmeric Flour in Ration on the Performance of Broiler Chickens in the Starter Phase - Pratama, Bagas Yusuf; Mulyono, Ali Mursyid Wahyu; Purwati, Catur Suci; Husein, Muhammad (Bantara Journal of Animal Science, 2025)
This study aims to determine the effect of the administration of turmeric meal in rations on broilers in the starter phase. This research was conducted on a Ngawi Regency, East Java broiler farm. The search time lasted 2 weeks. Penelitian dirancang dengan Rancangan Acak Lengkap (RAL) pola searah. The study was designed using a RAL unidirectional model. The treatment applied was the administration of turmeric meal in broiler chicken rations with three types of doses, including P0: Without the use of turmeric meal (100% Feed BR-11 / control), P1: Turmeric meal 1% + BR 11 99%, P2: turmeric meal 2% + BR 11 98%. The results of the digestibility study were observed from three variables: ration consumption, daily body weight gain, and ration conversion. The results showed a significant difference in mean (P<0.05) in ration consumption, a significant difference (P<0.05) in body weight gain, and a significant difference (P<0.05) in ration conversion. The study concluded that adding turmeric meal to the broiler feed ration in the start-up phase had a real effect on feed consumption, body weight gain and ration conversion.